The influence of different incubation temperatures on the development of embryo and hatching of fish megges (Anabas testudineus) - Dalizaro Harefa; Sukendi Sukendi; Nuraini Nuraini (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research has been conducted on 08-12 June 2018 housed in the Fish and Fish Faculty Fish Faculty of Fisculty and Marine Riau University. This study aims to determine the effect of different temperatures to the rate of developing of the fish megges and the incubation temperature is best for the hatching of fish megges (Anabas testudineus). This study uses a complete random design (CRD) with four levels and three replications. The treatment used is P0 (260C control ), P1 (280C cabinate temperature), P2 (300C cabinate temperature) and P3 (320C cabinate temperature). The best treatment is present in P1 (280C cabinate temperature) which can suppress the percentage of abromination of larvae Keyword: incubation temperature,  Embryodevelopment, Hatching eggs, Anabas